Correction to: Decision-making at the limit of viability: differing perceptions and opinions between neonatal physicians and nurses - Hans Ulrich Bucher; Sabine D. Klein; Manya J. Hendriks; Ruth Baumann-Hölzle; Thomas M. Berger; Jürg C. Streuli; Jean-Claude Fauchère; on behalf of the Swiss Neonatal End- (BMC, 2020)
After publication of our article [1] it was brought to our attention that we did not have permission to reproduce the questionnaire in Additional File 1.